The Impact of Gender Diversity on the Board of Directors on Firm Performance: Evidence from the Global Automotive Industry - Durmuş, Ahmet Fethi; Işık, Yusuf; Coşkun Arslan, Mihriban (International Review of Management and Marketing, 2026)
This study explores the impact of board-level gender diversity on corporate outcomes, based on data gathered from 39 leading firms in the international automotive sector be-tween 2020 and 2024. The Blau Index was employed to measure gender diversity, whereas company performance was evaluated through indicators like ROA, ROE, and the Tobin’s Q coefficient. Findings from the panel data analysis indicated that gender diversity had no statistically meaningful relationship with financial outcomes. On the other hand, the company size showed a statistically significant and positive effect, whereas the impact of leverage fluctuated based on the particular performance indicator used. Study results im-ply that although female board presence is often presumed to boost corporate perfor-mance, such an effect may not be universally applicable and depends on contextual fac-tors. While certain academic works report a notable link in this area, others assert that the direction of the effect varies—being either beneficial or adverse—based on industry type and cultural setting. This research yields valuable insights for decision-makers and cor-porate leaders aiming to assess how gender equality initiatives influence firm perfor-mance, particularly in alignment with sustainability goals and governance standards.